Antimicrobial Resistance Profiles in Enterococcus spp. Isolates From Fecal Samples of Wild and Captive Black Capuchin Monkeys (Sapajus nigritus) in South Brazil - Grassotti, Tiela Trapp; de Angelis Zvoboda, Dejoara; da Fontoura Xavier Costa, Letícia; de Araújo, Alberto Jorge Gomes; Pereira, Rebeca Inhoque; Soares, Renata Oliveira; Wagner, Paulo Guilherme Carniel; Frazzon, Jeverson; Frazzon, Ana Paula Guedes (Frontiers in Microbiology, 2018)
The environment, humans, and animals play an important role in the spread of antibiotic resistant bacteria. Enterococci are members of the gastrointestinal tracts of humans and animals, and represent important reservoirs of antibiotic resistance genes. Until today, few studies have examined antibiotic susceptibility in enterococci isolated from primates. Therefore, the present study investigated species distribution, antibiotic susceptibility, and resistance genes in enterococci isolated from wild and captive black capuchins monkeys (Sapajus nigritus) in Rio Grande do Sul, South Brazil. A total of 24 swabs/fecal samples were collected, including 19 from wild monkeys living in two forest fragments (São Sebastião do Caí - SSC and Santa Cruz do Sul - SCS), and five in captive (Parque Zoológico da Fundação Zoobotânica – ZOO), between August 2016 and November 2017. Fifteen colonies were randomly selected of each sample. Enterococci were identified, tested for susceptibility to 12 antibiotics; and screened for tet(S), tet(M), tet(L), msrC and ermB genes by PCR. Two-hundred ninety-six enterococci were isolated (SSC n=137; SCS n=86; ZOO n=73) and differences in Enterococcus species distribution were detected on three monkey groups, with low abundance in SCS (1 - D = 0.2), followed by ZOO (1 - D = 0.68) and SSC (1 – D = 0.73). The enterococci frequently recovered include; E. faecalis (42.6%), E. hirae (29.1%), and E. faecium (15.9%). Antibiotic-nonsusceptible was observed in 202 (67.9%) strains. The rate of nonsusceptibility to rifampicin, tetracycline, erythromycin, nitrofurantoin, chloramphenicol and ampicillin was 46%, 26%, 22% and 19%, 13%, 0.3% and 0.3%, respectively. All strains were susceptible to vancomycin, streptomycin, gentamycin and linezolid. Forty-three (14.52%) isolates were identified as multidrug resistant (MDR), and the highest number of MDR was observed in E. faecium recovered from wild monkeys living closer to a hospital and water treatment plant. Elevated rates of antibiotic-resistance genes msrC and tet(L) were isolates from ZOO. In conclusion, differences in the frequency of enterococci species, antibiotic-nonsusceptible and resistance genes in all groups of monkeys were identified. These data suggest that anthropogenic activities and/or resistome influence are presented in the primate gut communities.